Sustainable railway bridges with higher axle loads : monitoring examples from northern Sweden - Elfgren, Lennart; Enochsson, Ola; Täljsten, Björn; Paulsson, Björn (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2007)
Monitoring of several railway bridges has been carried out in northern Sweden in order to increase the allowable axle load. The work is part of a European Integrated Project "Sustainable Bridges - Assessment for Future Traffic Demands and Longer Lives". The paper describes the project and gives some examples of applications. Godkänd; 2007; Bibliografisk uppgift: Lennart Elfgren was awarded the price for Best Paper at IHHA STS Conference in Kiruna, Sweden 2007, and is entitled to free registration at the next IHHA Conference.; 20070708 (elfgren)